1975
DOI: 10.1139/z75-211
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the avian hematozoa of North America

Abstract: The literature pertaining to the prevalence of avian hematozoa in North America, north of Mexico, together with unpublished records from the files of the International Reference Centre for Avian Malaria Parasites, have been collated and analyzed with respect to the distribution of parasite genera by region, host family, and vertical stratification of nesting sites. The blood parasites of 57 026 birds of 388 species (representing 55 families) breeding in North America are the basis of this analysis. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
185
5
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(206 citation statements)
references
References 68 publications
14
185
5
2
Order By: Relevance
“…Even though the Neotropical region possesses the most diverse and richest avifauna of the world, this study indicated a low prevalence of blood parasites (15.9%), but represented a similar value to that recorded elsewhere in Central and South America (White et al 1978: it is far lower than that recorded for North America (Greiner et al 1975). Furthermore, the low number of double infections (4 individuals) found in this study, agrees with other reports from the Neotropics (Bennett & Sousa 1980).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Even though the Neotropical region possesses the most diverse and richest avifauna of the world, this study indicated a low prevalence of blood parasites (15.9%), but represented a similar value to that recorded elsewhere in Central and South America (White et al 1978: it is far lower than that recorded for North America (Greiner et al 1975). Furthermore, the low number of double infections (4 individuals) found in this study, agrees with other reports from the Neotropics (Bennett & Sousa 1980).…”
supporting
confidence: 91%
“…The families with the highest prevalence in this study were essentially the same as those in other studies in the Neotropics (White et al 1978), and the Neartic (Greiner et al 1975). It would appear that some aspect or habit of these birds enhances parasitism by haematozoans.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The Leucocytozoon sp. infection could have been acquired on the Nearctic breeding grounds where the overall prevalence of leucocytozoids exceeds 40% in the Swainson's thrush (Greiner et al, 1975 Haemoproteus sp. infection was recorded in the Magdalena valley (one bird infected, nϭ1) and eastern slope of the Andes (nϭ1), Plasmodium sp.…”
mentioning
confidence: 99%
“…The low overall prevalence of hematozoa in Colombia is typical for the Neotropics where the prevalence of blood parasites (approximately 10%) is significantly less than that in any other zoogeographical region (Greiner et al, 1975;White et al, 1978;Valkiū nas, 1997). Species of Haemoproteus, Plasmodium, Leucocytozoon, and Trypanosoma have been found in resident indigenous species of birds in the Neotropics (White et al, 1978;Sousa and Herman, 1982;Young et al, 1993;Valkiū nas, 1997) and thus are transmitted there.…”
mentioning
confidence: 99%